2019
DOI: 10.1128/aac.01577-18
|View full text |Cite
|
Sign up to set email alerts
|

The Antibiotic Trimethoprim Displays Strong Mutagenic Synergy with 2-Aminopurine

Abstract: We show that trimethoprim (TMP), an antibiotic in current use, displays a strong synergistic effect on mutagenesis in Escherichia coli when paired with the base analog 2-aminopurine (2AP), resulting in a 35-fold increase in mutation frequencies in the rpoB-Rifr system. Combination therapies are often employed both as antibiotic treatments and in cancer chemotherapy. However, mutagenic effects of these combinations are rarely examined. An analysis of the mutational spectra of TMP, 2AP, and their combination ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Mutations in rpoB can affect many operons or entire pathways and produce much larger benefits among different mutations. , The rpoB locus previously showed that it can increase the tolerance of E. coli to a variety of antibiotics and organic solvents. However, few mutations in the rpoB gene were reported to confer furfural tolerance in E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in rpoB can affect many operons or entire pathways and produce much larger benefits among different mutations. , The rpoB locus previously showed that it can increase the tolerance of E. coli to a variety of antibiotics and organic solvents. However, few mutations in the rpoB gene were reported to confer furfural tolerance in E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 allows for a comparison of the data in Figure 4 with the fingerprints of spontaneous mutations, those induced by trimethoprim (TMP), and those occurring in a mutT strain that has a high level of A:T→C:G mutations resulting from oxidative damage to a DNA precursor. Although we have published an earlier version of each of the three spectra shown in Figure 4 (D'Souza et al, 2019; Garibyan et al, 2003), there was concern that in our previous studies we may not have picked the very small colonies, so we redid the spectra of mutT and TMP, making sure to not overlook any initially small colonies (see Section 2). The new spectra of mutT and TMP are shown here (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…There are three main types of chemical agents that are traditionally used to induce mutations, including alkylating compounds, base analogues, and antibiotics, each with different effects. ,, The effect of mutagenic agents is caused by lesions or a modification in the base sequence of the DNA molecule, which leads to a misreading during repair and replication. Alkylating agents mainly modify the bases and phosphoric acid on DNA molecules with alkyl groups.…”
Section: Library Construction Based On Traditional Microbial Mutagene...mentioning
confidence: 99%
“…Tautomerism occurs in keto and enol forms in pyrimidine molecules, while amino and imino groups are allosteric in purine molecules. Some antibiotics such as trimethoprim can also cause DNA damage or even strand-beaks at a sufficiently high concentration . A successful case of using chemical mutagenesis was reported by Smith and colleagues, who developed an isobutanol-producing strain of Escherichia coli by combining NTG mutagenesis with ALE.…”
Section: Library Construction Based On Traditional Microbial Mutagene...mentioning
confidence: 99%
See 1 more Smart Citation